Readiness of Philippine cities to smart city development - Tatum P. Ramos; Pauline Joy M. Lorenzo; Jenica A. Ancheta; Marife Magno-Ballesteros (Philippine Institute for Development Studies (PIDS), 2021)
Smart city development is recognized as a potential solution to urbanization issues, but a disconnect comes along with the vagueness in smart city elements and pathways. The use of the term smart city by some local government units in the Philippines evokes a utopia - a local sphere with numerous positive developments that will greatly benefit the constituents. The lack of studies providing evidence on the readiness of Philippine cities to smart city development, however, prevents the establishment of the cities capacities to address urban challenges with their initiatives. This study aims to examine whether Philippine cities are prepared for smart city development by answering three policy questions: (1) What drives Philippine LGUs towards the implementation of smart city initiatives?; (2) What is the extent of smart city development among Philippine cities?; and (3) How can the Philippine government facilitate the development of smart cities?. A desk review of smart city initiatives in some Philippine and international cities was carried out, and interviews were conducted with stakeholders from selected cities in Luzon, Visayas, and Mindanao. Based on the findings, the Philippines has started to tread the path towards building smart cities, and some Philippine cities already exhibit preparedness for smart city development. Smart city enablers are already in place, but the degree to which they are applied is not very extensive. Both at the national and local levels, there are significant challenges that need to be addressed. These include issues related to data interoperability, national standards on data repositories and application programming interfaces, risk mitigation strategies, monitoring and assessment, accountability, and others. If such issues are unaddressed, there will be a risk of not fully realizing the potential of smart city initiatives being implemented in the Philippines.
Keywords: 330; smart city; digital city; intelligent city; local government; Philippine cities; sustainable city